Seasonal shift of foraging habitat among farmland breeding Eurasian Curlews Numenius arquata - de Jong, Adriaan (Ornis Norvegica, 2012)
The importance of landscape heterogeneity for farmland birds is widely recognized, but the underlying processes remain unclear. Here I investigate the distribution of foraging and non-foraging Eurasian Curlews over agricultural treatment classes during the breeding season. The results show that Eurasian Curlews used grassland for foraging early in the breeding season but shifted to cereal fields later. Contrastingly, the distribution of non-foraging Eurasian Curlews over treatment classes rarely deviated from random. I conclude that relative foraging habitat quality changed among the investigated agricultural treatment classes and that landscapes containing more than one treatment class have higher overall quality for Curlews. Preserving or creating landscapes with a mix of different kinds of commercially managed fields is a relatively cheap and easily accepted farmland bird conservation measure.